SIMAKOM Implementation Alternatives to Improve the Quality of Financial Services in Islamic Private Schools - Hadian Firman Syahreza; Wildansyah Lubis; Sriadhi Sriadhi; Yuniarto Mudjisusatyo; Eka Daryanto; Arif Rahman; Nathanael Sitanggang (Asia Pacific Journal of Management and Education (APJME), 2025)
Effective and efficient school financial management is crucial for enhancing the quality of educational services. However, many schools still rely on manual systems, which can lead to errors and delays in financial processes. This study aims to examine how the SIMAKOM application can serve as an alternative financial management system to improve the quality of financial services in Integrated Islamic Private Schools. A mixed methods approach (quantitative and qualitative) was employed, with data collected through questionnaires and analyzed using descriptive methods. The results indicate that the SIMAKOM application enhances system quality, user quality, service quality, perceived benefits, and user satisfaction. The quantitative findings include a system quality score of 3.811 and a user satisfaction score of 3.931, based on responses from 93 participants. The qualitative component involved interviews and triangulation to support and enrich the quantitative data. Overall, the SIMAKOM application is shown to be an effective alternative for improving the quality of school financial services. This study contributes to the development of high-quality financial management systems in educational institutions and can serve as a reference for other schools seeking to enhance their financial service quality through digital solutions.